Strategic Leadership Analysis of the Minister of Education in Face-To-Face Learning Decisions in the Crisis of Covid-19 - Efriska Ginasti Mayangsari; Amy Yayuk Sri Rahayu; Zairyanto Poedjiaty (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The Ministry of Education and Culture implementing Distance Learning or learning from due to pandemic issued. This article examines the ministry's decision with a qualitative approach with the background that over the course of the learning from home process, the Indonesian Child Protection Commission (KPAI) has received two hundred and thirteen cases of learning from home complaints from both parents and students. As the Ministry of Education, Culture, Research and Technology to make definite decisions based on existing research to achieve strategic leadership, the research conducted the Minister needs to run limited face-to-face learning policy in support of the decision. Nadiem Makarin as the minister applies leadership collaborative activities such as facilitating processes, mediating and fostering relationships with stakeholders.